Factors influencing tobacco smoking among men aged 15–49 years in Nepal - David Mensah Otoo; Samuel Salu; Prince Tsekpetse; Othniel Nee-Koteifio Kotey (Scientific Reports)
Abstract Tobacco use in Nepal represents a significant public health challenge, with a prevalence of 28% reported among men. Despite the recognition of tobacco as a leading preventable cause of death globally, there remains a notable gap in understanding how shifts in social, economic, and public health landscapes since 2016 have influenced the predictors of tobacco use among Nepalese men. This study aims to investigate which factors still significantly influence the persistent trend in tobacco use among men in Nepal. This study utilized data from the male recode (MR) file of the 2022 Nepal DHS. The analysis included 4,913 men aged 15–49 years. A multilevel logistic regression analysis was performed across four models to determine factors influencing tobacco smoking among respondents. Results were presented as adjusted odds ratios (aORs) with 95% confidence intervals (CIs) and intraclass correlation coefficients. The prevalence of tobacco smoking among respondents was 28.0%. Men aged 35–44 (aOR = 0.80; 95% CI [0.82–0.98]) and 45–49 (aOR = 0.70; 95% CI [0.53–0.99]) had reduced odds of using tobacco compared to younger men aged 15–24. Men with higher educational levels had decreased odds of smoking tobacco (aOR = 0.40; 95% CI [0.24–0.61]) as compared to men with no formal education. Men who lived in hilly (aOR = 0.70; 95% CI [0.50–0.92]) and terai regions (aOR = 0.70; 95% CI [0.50–0.96]) also had reduced odds of smoking tobacco as compared to those living in mountainous areas. However, the odds of smoking tobacco were highest among men who were involved in skilled manual labor (aOR = 2.60; 95% CI [1.89–3.61]) relative to those who were not working. Men who consumed alcohol had higher odds of smoking tobacco (aOR = 3.80; 95% CI [3.28–4.40]) than those who did not consume alcohol. Men in the richest wealth category also showed increased odds of smoking tobacco (aOR = 1.40; 95% CI [1.02–1.89]) compared to those in the poorest category. Moreover, men who reported good (aOR = 1.20, 95% CI [1.02–1.38]) or moderate (aOR = 1.60, 95% CI [1.13–2.14]) health status had higher odds of smoking tobacco compared to those who reported bad health status. The study concluded that factors such as age, education, occupation, alcohol consumption, self-reported health status, ecological region, and wealth index were factors that significantly influenced tobacco smoking among men in Nepal. Nepal must strengthen tobacco control by enforcing regulations, adopting new policies, expanding cessation support, and increasing public awareness.